PERAN NAZHIR DALAM PENGELOLAAN WAKAF PRODUKTIF PADA YAYASAN KESEJAHTRAAN NURUL BAHAR TOMALOU KOTA TIDORE KEPULAUAN - Gunawan, Fahmi; Mahmud, Adnan; Umasugi, Nirwan (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
Waqf management lies in the existence of waqf managers, especially nazhir and a solid work team to maximize the role of waqf. If waqf is managed professionally, then it will become a potential Islamic institution that functions to fund and develop the people's economy. Therefore, the progress of waqf is largely determined by the good and bad management of waqf management. And also the waqf institution is a religious institution that has potential and economic benefits that need to be managed effectively and efficiently for the benefit of worship and advancing public welfare. The social welfare of the community that is expected cannot be realized optimally if Nazhir does not carry out his duties optimally, what is Nazhir's role in managing productive waqf at the Nurul Bahar Tomalou Welfare Foundation, Tidore City, the purpose of management is to realize the welfare of the people. Waqf has a dual function, namely the function of worship and social function. In the function of worship, waqf aims to be a provision for wakif in the afterlife because the reward continues to flow during mawqûf bih. In its social function, waqf plays a role in creating the welfare of the people when the nazhir's role is in optimal management by the nazhir. In accordance with the law. The research used is field research, namely research that seeks to find primary data obtained directly from productive waqf implementation activities. The results of research on the role of a nazir on waqf management carried out by nazirs in a professional manner provide opportunities for waqf development to be more productive, as well as provide opportunities for the application of modern management principles. Within this framework, nazhir should try to show the best possible waqf performance.